A new genus and two new species of freshwater Gastropoda from the Ceyhan River Basin in the eastern Mediterranean (Mollusca: Gastropoda: Truncatelloidea). Issue 1 (2nd January 2019) - Emre Gürlek, Mustafa
Abstract : In a survey of the mollusc fauna of the Ceyhan River Basin, including rivers, natural lakes, dam lakes and springs between June 2008 and September 2014, a total of 20 species of Gastropoda and 8 species of Bivalvia were identified. Two of these species are new to science, and for one of them a new genus is erected: the hydrobiid Hemite ceyhanensis gen. n., sp. n., and the bithyniid Pseudobithynia cocussusica sp. n. http://www.zoobank.org/urn:lsid:zoobank.org:pub:DE5FFC19-13CD-4B81-B74E-80059E781518